Interpersonal Communication to Build Commitment in Serious Courtship - Naome, Elisabeth; Naryoso, S.Sos, M.Si, Agus (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Lots of adults being in relationship only for having fun and for eliminating „single‟ status with no seriousness for both future. In a relationship just for having fun often cause conflict within relationship because they have no trust and commitment which are the foundation. Interpersonal communication determine the success or failure of the couple to maintain and achieve one common goal. The purpose of this study was to understand interpersonal communication to build commitment in serious courtship for couples. This is a qualitative research with interpretative paradigm and phenomenological methodology. Research subjects are two couples which at least one year of dating. The theory in this research are Maintenance Relationship from Laura Stanford & Canary and Self Disclosure from Joseph Luft & Harry Ingham. Research shows that couples has interpersonal communication in self disclosure, self concept, verbal and nonverbal context in a good level. Openness between couples make them closer and getting more deeper private information of partners. Couples has positive self concept of them self. Verbal communication is often and nonverbal communication is for support. Nonverbal capable of being a lie detector between couples. In maintenance relationship, couples has high level of trust. They also keep and doing their commitment. The conclusions of this research is that low intensity of interpersonal communication can cause conflicts for couple. Moreover, one of the forms of interpersonal communication to build commitment in serious courtship is self disclosure from both couple. The quality of verbal and nonverbal communication necessary to avoid conflicts. Also a positive self concept is necessary to improve the relationship quality. Couple indicates love through verbal and nonverbal communication which can be seen through each other‟s way to reveal their feelings to their partner. And nonverbal can be seen through eye contact, distance proximity and touch when they met. Mutuality turn “me” into “us” and it can increase intimacy